2019
DOI: 10.3390/biom9040147
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered Proteins in Chronic Diseases

Abstract: It is now increasingly evident that a large fraction of the human proteome comprises proteins that, under physiological conditions, lack fixed, ordered 3D structures as a whole or have segments that are not likely to form a defined 3D structure [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…This result is particularly interesting because misexpressed, misprocessed and dysregulated IDPs are highly prone to engage in promiscuous interactions with other proteins, DNA or RNA molecules, causing pathological states. [ 127 ] Moreover, an “evolutionary biochemistry” approach based on molecular modelling and NMR experiments suggests that interactions in a proteome start with low‐affinity IDPs that become structured and specific through progressive mutations. [ 128 ] Thus, the promiscuity of IDP and their ability to interact at all levels in protein‐protein, protein‐DNA and protein‐RNA layers could be the origin of the versatility of gene networks but also its weakness.…”
Section: Structural Disorder and Rna‐binding Ability Are Key Determinmentioning
confidence: 99%
“…This result is particularly interesting because misexpressed, misprocessed and dysregulated IDPs are highly prone to engage in promiscuous interactions with other proteins, DNA or RNA molecules, causing pathological states. [ 127 ] Moreover, an “evolutionary biochemistry” approach based on molecular modelling and NMR experiments suggests that interactions in a proteome start with low‐affinity IDPs that become structured and specific through progressive mutations. [ 128 ] Thus, the promiscuity of IDP and their ability to interact at all levels in protein‐protein, protein‐DNA and protein‐RNA layers could be the origin of the versatility of gene networks but also its weakness.…”
Section: Structural Disorder and Rna‐binding Ability Are Key Determinmentioning
confidence: 99%
“…Generally, IDPs/IDRs are enriched in proteins involved in signaling and regulatory functions, including transcription regulation, cell cycle, mRNA processing, scaffolding, and apoptosis . Consequently, dysregulation of IDPs/IDRs are associated with a variety of human diseases . Most recently, many IDPs/IDRs are found to be able to undergo liquid–liquid phase separation (LLPS), which is related to the assembling of membraneless organelles in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…6,14,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] Consequently, dysregulation of IDPs/IDRs are associated with a variety of human diseases. [32][33][34][35][36][37][38][39][40][41][42][43][44] Most recently, many IDPs/IDRs are found to be able to undergo liquid-liquid phase separation (LLPS), which is related to the assembling of membraneless organelles in vivo. [45][46][47][48][49][50][51][52][53] So far, studies on IDPs/IDRs have greatly extended our understanding on the sequence-structurefunction relationship of proteins.…”
mentioning
confidence: 99%
“…Most of the proteins associated with diseases, such as cancer, AD, PD, diabetes, and cardiovascular disease are either IDPs or contain long IDPRs, and misbehavior or mutations in the IDPs/IDPRs have broad involvement in the pathogenesis of these diseases [44][45][46][47][48][49]. From overall analysis, we found that most of the UPS proteins are intrinsically disordered and are closely linked with the pathophysiology of many diseases, such as cancer, AD, PD, ALS, HD, etc.…”
Section: Intrinsic Disorder In the Proteins Of Ubiquitin Proteasomal mentioning
confidence: 93%
“…Intrinsically disordered proteins (IDPs) and IDP regions (IDPRs) are the proteins or regions of proteins that lack well-defined, three-dimensional unique structures and show structural transition upon binding with their biological partners [44][45][46][47][48][49]. IDPs/IDPRs are commonly found in all organisms, being more abundant in eukaryote proteomes [50][51][52].…”
Section: Introductionmentioning
confidence: 99%